Model Pembelajaran Kitab Tafsir Jalalain di Pondok Pesantren As-Syifa’ Ul Islamiyah: Studi Kualitatif Tradisi Bandongan, Sorogan dan Musyawarah - Hairom; Nasrullah; Fiddian Khairudin (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2026)
This study aims to describe the implementation of Tafsir al-Jalalain learning methods and to analyze its exegetical and functional reception at As-Syifa’ Ul Islamiyah Islamic Boarding School. This research employs a qualitative approach with a field research design. Data were collected through participant observation, in-depth interviews, and documentation, and analyzed using descriptive-analytical techniques, including data reduction, data display, and conclusion drawing. The findings reveal that the learning process integrates three main methods—bandongan, sorogan, and musyawarah—which complement each other in developing students’ comprehensive understanding. The exegetical reception of students tends to be textual-linguistic and authoritative, while its functional reception is reflected in its role as a moral guideline, character-building tool, and a symbol of the continuity of Islamic scholarly tradition. This study highlights that the integration of classical learning methods effectively connects cognitive, affective, and practical dimensions simultaneously. Therefore, strengthening integrative tradition-based learning models is essential to maintain the relevance of Islamic boarding school education in the contemporary era.